1981
DOI: 10.3133/pp1188
|View full text |Cite
|
Sign up to set email alerts
|

Geology and origin of the Chilean nitrate deposits

Abstract: ____________________________________________________________________ 1 Introduction __________________________________________________________________ 1 Location _______________________________________________________ 2 Acknowledgments ___________________________________________________________ 3 Geomorphology _____________________________________________________________ 3 Climate, vegetation, and soil microorganisms ______________________________________________ 8 Geology of the nitrate deposits _____________… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
269
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(277 citation statements)
references
References 45 publications
6
269
0
2
Order By: Relevance
“…Naturally occurring ClO 4 -from the Atacama is widely known (6). The Atacama Desert nitrate deposits of northern Chile also contain naturally occurring ClO4 -and other oxyanions such as IO3 -, CrO4 2-, and Cr2O7 2-.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally occurring ClO 4 -from the Atacama is widely known (6). The Atacama Desert nitrate deposits of northern Chile also contain naturally occurring ClO4 -and other oxyanions such as IO3 -, CrO4 2-, and Cr2O7 2-.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, potassium perchlorate is a key ingredient in the production of fireworks, explosives, road flares, and other minor uses (22). Natural sources of perchlorate were generally thought to be restricted to fertilizers mined from Chilean caliche deposits (23). However, recent studies suggest a possible atmospheric origin for background levels of perchlorate, formed from chloride or hypochlorite during atmospheric lightning discharges or from reactions involving ozone, solar energy, and chloride (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…Chilean nitrate has long been known to be a natural source of perchlorate (20). A recent comprehensive evaluation has shown that, with the exception of fertilizers derived from Chilean nitrate, fertilizers are not a significant source of perchlorate to the environment (21).…”
Section: Introductionmentioning
confidence: 99%